Intragastric acidity as a predictor of the success of Helicobacter pylori eradication: a study in peptic ulcer patients with omeprazole and amoxicillin. (July 1995) - Labenz, J; Stolte, M; Blum, A L; Jorias, I; Leverkus, F; Sollböhmer, M; Bertrams, J; Börsch, G
Abstract : Omeprazole plus amoxicillin cures Helicobacter pylori infection. The hypothesis was tested that low acidity is a predictor of outcome. Fifty patients with relapsing or complicated, or both H pylori positive duodenal (n = 25) or gastric ulcer (n = 25) were randomly treated with either omeprazole 20 mg twice daily plus amoxicillin 1 g twice daily or with omeprazole 40 mg twice daily plus amoxicillin 1 g twice daily over two weeks. After one week of combined treatment, a 24 hour gastric pH measurement was performed in all patients. H pylori cure rate was 67%. Patients who later turned out to be cured had higher pH values during night time and after meals (p < 0.05). In an explorative analysis drug compliance, smoking, location of the ulcer (duodenum versus stomach), age, and grade of body gastritis were additional predictors of the outcome. Smoking (p = 0.006), compliance (p = 0.037), duodenal ulcer disease (p = 0.065), and young age (p = 0.021) were related to high acidity. In conclusion, the success of eradication treatment with omeprazole and amoxicillin in ulcer patients infected with H pylori depends on intragastric pH. Drug compliance, smoking habits, location of ulcer, age, and activity of body gastritis are other predictors and in part related to intragastric acidity.